El discurso digital - Martínez Menéndez, Pablo (Verba hispanica, 2025)
In the teaching of Spanish as a Foreign Language (ELE), numerous preju-dices persist regarding both the type of language students should learn and the methods by which they should learn it. Methodologically, the field has shifted from an elitist focus on written language to approaches emphasizing communicative competence, at times minimizing or excluding grammar instruction. Likewise, normative Spanish has often been prioritized over colloquial registers, and northern Peninsular Spanish over other varieties. Structural gap-filling exercises, as well as playful or game-like activities, have also faced criticism from scholars in second language acquisition.Similar resistance can be expected when introducing digital discourse into Spanish as a Foreign Language instruction. Nevertheless, this type of discourse offers several advantages, which this article aims to explore – including access to a variety of Spanish increasingly used in real communicative con-texts and the opportunity to engage learners in spaces already familiar to digital natives, who routinely employ their own language in such environments.
Keywords: besedilna kompetenca; ciberhabla; competencia textual; cyber-speech; ELE; intercultural; kibernetski govor; medkulturnost; multimodalidad; multimodality; multimodalnost; Spanish as a Foreign Language; španščina kot tuji jezik; textual competence